Environmental pollution in the Mantaro Valley. Medical report (La Oroya, 1926) - Tácunan Bonifacio, Santiago (2012)
This paper analyzes one of the first me dical reports from the beginning of the twentieth century that highlights the environmental pollution produced by the mining company Cerro de Pasco Copper Corporation in La Oroya (Mantaro Valley, 1926).